Pengaruh Pemberian Ekstrak Kencur (Kaempferia galanga L.) terhadap Peningkatan Zona Hambat Pertumbuhan Bakteri Staphylococcus aureus - Linda Putri Utami; Peter Gunawan Tandean; Liliawanti Liliawanti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
The prevalence of infectious diseases in Indonesia is still relatively high, for example Infection caused by Staphylococcus aureus. Indonesia has many traditional plants that can be used for herbal treatments containing tannins, flavonoids, and essential oils which have relatively high antibacterial activity by forming inhibitory zones in the Staphylococcus aureus bacteria which are the cause of skin infections food poisoning to systemic infections. Thereforekencur can be used as an alternative medicine. This study was intented to determine the effect of giving kencur extract (Kaempferia galanga L.) In inhibiting the growth of Staphylococcus aureus bacteria. This study was experimental laboratory used plate diffusion method of “Postest Ony Control Group Design” design. There were 7 groups, 5 treatment groups and 2 control groups. The concentration of treatment group was 100%, 50%, 25%, 12,5%, 6,25% while for positive control using amoxicillin 25μg and aquadest as negative control. The bacterial used were Staphylococcus aureus. The results showed that kencur extract (Kaempferia galanga L.) had an antibacterial effect in inhibiting the growth of Staphylococcus aureus bacteria.With a value of p = 0.001 or p <α. kencur extract (Kaempferia galanga L.) has an antibacterial effect in inhibiting the growth of Staphylococcus aureus bacteria.